The Role of Philosophy of Science in Developing Students’ Critical and Creative Thinking Skills - Rifadli Amin DG. M; Nurasma Ila Ismail; Mustamin Giling (International Islamic Studies Development and Research Center (IISDRC), 2026)
The era of disruption, marked by technological revolutions, an information explosion, and complex social dynamics, calls for the emergence of Muslim intellectuals who are not only religious but also adaptable, critical, and creative. This article aims to analyze the strategic role of the Philosophy of Science course in developing students’ critical and creative thinking patterns as a foundation for building adaptive intellectual capacity. The research employs a qualitative approach using the case study method, involving participatory observation in Philosophy of Science classes, curriculum document analysis, and in-depth interviews with fifteen students and five instructors. The research findings indicate that effective Philosophy of Science instruction serves as a metacognitive toolkit that empowers students, first to conduct critical analysis of the structure of knowledge, underlying assumptions, and the validity of arguments, whether in religious texts or contemporary issues; second, to develop intellectual creativity by formulating philosophical questions, mapping scientific problems in a multidisciplinary manner, and envisioning alternative solutions. The implications of this study indicate that the philosophy of science plays a very important role in fostering critical thinking among students, although in practice, some instructors still limit students’ thinking by relying solely on a single argument.